2014
DOI: 10.1111/apt.12861
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of breath volatile organic compounds reveals unique breathprints in children with inflammatory bowel disease: a pilot study

Abstract: Background Breath testing is becoming an important diagnostic method to evaluate many disease states. In light of rising healthcare costs, is important to develop a simple non-invasive tool to potentially identify pediatric patients who need endoscopy for suspected inflammatory bowel disease (IBD). Aim The primary aim of this study was to analyze exhaled volatile organic compounds (VOCs) to evaluate for the presence of a unique breath pattern to differentiate pediatric patients with (IBD) from healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 27 publications
(29 reference statements)
1
56
0
Order By: Relevance
“…We agree that analytical techniques that are able to identify single compounds, such as single ion flow tube mass spectrometry 4,5 are complementary to the electronic nose technology. Examples of this approach include the development of hand held breath sensors for the diagnosis of asthma after identifying the key VOC in single analyte studies.…”
supporting
confidence: 52%
“…We agree that analytical techniques that are able to identify single compounds, such as single ion flow tube mass spectrometry 4,5 are complementary to the electronic nose technology. Examples of this approach include the development of hand held breath sensors for the diagnosis of asthma after identifying the key VOC in single analyte studies.…”
supporting
confidence: 52%
“…Finally, in a pilot study using breath metabolomic analysis, it was demonstrated that children with IBD have a unique breath profile that can separate them from HC children [50] .…”
Section: Ibd Disease Signature: Case-control Studiesmentioning
confidence: 99%
“…With this best-of-both-worlds approach, we are able to identify unique "breathprints" in patients with liver disease ( fetor hepaticus) as well as those for heart and lung disease. 85,88,93,94 We are further able to analyze these patterns to identify single molecules in the breath of these patients and link them to the underlying pathobiology of the disease. 85,86,88,95,96 In a single-center cohort study of PAH patients, we correlated exhaled-breath VOCs with clinical parameters.…”
Section: Exhaled-breath Analysismentioning
confidence: 99%